Le cellule staminali mesenchimali nel trattamento delle pseudoartrosi - Rizzo, Maria; Romano, Luigi; Tammaro, Nicola (Lo Scalpello - Journal, 2019)
Bone regeneration is a complex physiological process of bone formation, which can be seen during normal fracture healing. However, there are clinical conditions in which failure of the biological processes of fracture-healing is evident, such as with nonunion. Many biological treatments to prevent or treat nonunions are emerging in clinical use, including stem-cell treatment: there is evidence showing that mesenchymal stromal cells (MSC) may constitute a potential therapeutic strategy to induce bone regeneration.